Enhanced protective immunity against spring viremia of carp virus infection can be induced by recombinant subunit vaccine conjugated to single-walled carbon nanotubes. Issue 42 (8th October 2018) - Zhang, Chen; Li, Lin-Han; Wang, Jin; Zhao, Zhao; Li, Jian; Tu, Xiao; Huang, Ai-Guo; Wang, Gao-Xue; Zhu, Bin
Highlights: SWCNTs can be used as carriers for subunit vaccine. SWCNTs-subunit vaccine can enhance the immunological activity against SVCV infection. SWCNTs based subunit vaccine have prospects for application to aquatic vaccine. Abstract: As a successful prevention strategy for controlling the highly contagious and pathogenic disease of spring viremia of carp (SVC), DNA vaccines reported in recent years could trigger protective responses against SVC with the means of injection. However, there remains many concerns and uncertainties related to DNA vaccination as well as injection is labor intensive, costly and not suitable to vaccinate large numbers of fish. Therefore, more efficient and safe prophylactic measures should be urgently investigated. In this research, single-walled carbon nanotubes (SWCNTs) as the candidate SWCNTs-pET32a- G subunit vaccine carrier were administrated via bath (1, 5, 10, 20, 40 mg L −1 ) or injection (1, 4, 8, 12, 20 μg) in common carp juvenile, and the different immune treatments to induce immunoprotective effect were analyzed. The results showed that SWCNTs-pET32a- G could enter fish body after immersion for 10 h, furthermore, compared to control groups, antibody levels, the non-specific immune parameters (complement activity, superoxide dismutase activity and alkaline phosphatase activity), and immune-related genes (especially the TNF-α and IFNg2b ) in vaccinated groups were significantly enhanced in fish immunized with SWCNTs-subunit vaccine. In addition, as a promising carrier, SWCNTs can increase the immune protective effect of naked subunit vaccine by ca. 16% in bath immunization group and by ca. 23% in injection group. This study suggests that SWCNTs-vaccine may represent a potentially efficient immersion vaccine against viral pathogens of fish in the future.